Pengaruh Opinion Shopping dan Ukuran Perusahaan Terhadap Audit Going Concern Pada Perusahaan Subsektor Batubara Di Bursa Efek Indonesia - Aprizal Rosadian; Mursalin Mursalin; Muhammad Aidil Fitriansyah (Jurnal Media Akuntansi (Mediasi), 2022)
ABSTRACT Going concern audits can be influenced by opinion shopping and company size. Opinion Shopping shows the change of independent auditors for the following year if the current year the company gets a going concern audit opinion. The larger the size of the company, the lower the acceptance of going concern audit opinion. This study aims to determine the effect of opinion shopping and company size individually or jointly on going concern audits of coal subsector companies on the Indonesia Stock Exchange (IDX). The data used is secondary data. The population in this study are all coal sub-sector companies on the Indonesia Stock Exchange. The sampling technique used purposive sampling in order to obtain 13 coal sub-sector companies on the Indonesia Stock Exchange during the 2016–2020 period. Data collection techniques using documentation techniques. The data analysis technique used logistic regression analysis. Based on the hypothesis test, it can be concluded that individually there is no effect of opinion shopping on going-concern audits, there is an effect of firm size on going-concern audits. Taken together, there is an effect of opinion shopping and company size on going concern audits. Keywords: Opinion Shopping, Company Size, Audit Going Concern  ABSTRAK Audit going concern bisa dipengaruhi oleh opinion shopping dan ukuran perusahaan. Opinion Shopping menunjukan pergantian auditor independen untuk tahun berikutnya apabila tahun berjalan perusahaan mendapat opini audit going concern. Semakin besar ukuran perusahaan maka semakin rendah penerimaan opini audit going concern. Penelitian ini bertujuan untuk mengetahui pengaruh opinion shopping dan ukuran perusahaan secara individu maupun bersama-sama terhadap audit going concern pada perusahaan subsektor batubara di Bursa Efek Indonesia (BEI). Data yang digunakan yaitu data sekunder. Populasi dalam penelitian ini adalah seluruh perusahaan subsektor Batubara di Bursa Efek Indonesia. Teknik pengambilan sampel menggunakan purposive sampling sehingga diperoleh 13 perusahaan subsektor Batubara di Bursa Efek Indonesia selama periode 2016–2020. Teknik pengumpulan data menggunakan teknik dokumentasi. Teknik analisis data menggunakan analisis regresi logistik. Berdasarkan uji hipotesis dapat disimpulkan secara individu tidak ada pengaruh opinion shopping terhadap audit going concern, ada pengaruh ukuran perusahaan terhadap audit going concern. Secara bersama-sama ada pengaruh opinion shopping dan ukuran perusahaan terhadap audit going concern. Kata Kunci: Opinion Shopping, Ukuran Perusahaan, Audit Going Concern